Vitamins as Active Agents for Highly Emissive and Stable Nanostructured Halide Perovskite Inks and 3D Composites Fabricated by Additive Manufacturing. (2nd December 2022) - Recalde, Ileana; Gualdrón‐Reyes, Andrés. F.; Echeverría‐Arrondo, Carlos; Villanueva‐Antolí, Alexis; Simancas, Jorge; Rodriguez‐Pereira, Jhonatan; Zanatta, Marcileia; Mora‐Seró, Iván; Sans, Victor
Abstract: The use of non‐toxic and low‐cost vitamins like α‐tocopherol (α‐TCP, vitamin E) to improve the photophysical properties and stability of perovskite nanocrystals (PNCs), through post‐synthetic ligand surface passivation, is demonstrated for the first time. Especially interesting is its effect on CsPbI3 the most unstable inorganic PNC. Adding α‐TCP produces that the photoluminescence quantum yield (PLQY) of freshly prepared and aged PNCs achieves values of ≈98% and 100%, respectively. After storing 2 months under ambient air and 60% relative humidity, PLQY is maintained at 85% and 67%, respectively. α‐TCP restores the PL features of aged CsPbI3 PNCs, and mediates the radiative recombination channels by reducing surface defects. In addition, the combination of α‐TCP and PNCs facilitates the chemical formulation to prepare PNCs‐acrylic polymer composites processable by additive manufacturing. This enables the development of complex shaped parts with improved luminescent features and long‐term stability for 4 months, which is not possible for non‐modified PNCs. A PLQY ≈92% is reached in the 3D printed polymer/PNC composite, the highest value obtained for a red‐emitting composite solid until now as far as it is known. The passivation shell provided by α‐TCP makes that PNCs inks do not suffer any degradation process avoiding the contact with the environment and preserve their properties after reacting with polar monomers during composite polymerization. Abstract : In this study, the use of non‐toxic and low‐cost vitamins such as α‐tocopherol is highlighted to achieve high‐quality CsPbX3 perovskite nanocrystals (PNCs) with enhanced optical performance. This combination facilitates the chemical formulation to prepare highly emissive and long‐term stable 3D printed polymer/PNCs composites processable by additive manufacturing, showing a high potentiality for scalable and robust optoelectronics.